APPLICATION OF TURIMAN JALE AS AN INNOVATION TO IMPROVE CROP PRODUCTIVITY AND DRYLAND FARMERS’ INCOME IN GUNUNG KIDUL YOGYAKARTA: turiman jale, productivity, income, dry land. - Eko Srihartanto; Arif Anshori (Agric, 2022)
Maize and soybean have been widely cultivated in dryland. However, their productivity is relatively low. Turiman Jale cropping system was then established as an innovation to increase productivity by intercropping maize and soybean with proper arrangement of population and cultivars used. This study aimed to determine the best Turiman Jale cropping system model for increasing crop productivity, thereby improving the income of dryland farmers. The research was conducted during the second planting season 2019/2020 at the dryland of the Sadar Karya II Farmers Group, Sumberwojo, Sidorejo, Ponjong, Gunungkidul. It was arranged in a Randomized Complete Block Design (RCBD) consisting of 10 cropping systems, namely Jale 2:3 (cv. P36-Dega1)(40x20cm), Jale 2:3 (cv. P36-Dega1)(40x30cm), Jale 2:3 (cv. P36 -Dega1)(40x40cm), Jale 2:4 (cv. Bisi2-Dega1)(40x30cm), Jale 3:3 (cv. Bisi2-dega1)(40x30cm), Jale 2:6 (cv. NK212-Dega1)(40x30cm), maize monoculture (cv. Bisi2) (80x40x30cm), maize monoculture (cv. NK212) (80x40x30cm), maize monoculture (cv. Pioner36) (80x40x30cm), and soybean monoculture (cv. Dega1)(30x15cm). Observation was made on plant growth and yield variables. Land Equivalent Ratio (LER), Area Time Equivalent ratio (ATER), R/C ratio, B/C ratio, and Marginal Benefit Cost Ratio (MBCR) were also measured. The data were analyzed using ANOVA then further tested for orthogonal contrast and Tukey’s test with 5% significance level. The results showed that Jale 3:3 (Bisi2-Dega1)(40x30cm) resulted in the highest productivity, which was 5.890 ton ha-1 for maize and 2.209 ton ha-1 for soybean, with high LER of 1.79, high ATER of 1.90, R/C ratio of 2.33, B/C ratio of 2.39 and MBCR of 1.23, making it profitable and feasible.